1986
DOI: 10.1111/j.1365-2133.1986.tb06236.x
|View full text |Cite
|
Sign up to set email alerts
|

An open study of vitamin D3 treatment in psoriasis vulgaris

Abstract: Active forms of vitamin D3, 1 alpha-hydroxyvitamin D3 and 1 alpha,25-dihydroxyvitamin D3, were administered in an open-design study to 40 patients with psoriasis vulgaris in three ways: to 17 patients 1 alpha-hydroxyvitamin D3 was given orally at a dose of 1.0 micrograms/day for 6 months, to four patients 1 alpha,25-dihydroxyvitamin D3 was given orally at a dose of 0.5 microgram/day for 6 months, and 19 patients were given 1 alpha,25-dihydroxyvitamin D3 applied topically at concentration of 0.5 microgram/g of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(78 citation statements)
references
References 40 publications
1
76
0
Order By: Relevance
“…Therefore, it is speculated that VitD3 derivatives may be useful for the therapy of Th1-dependent immune diseases. Indeed, recently, it has been reported that VitD3 derivative is effective against psoriasis in human and experimental autoimmune encephalomyelitis in animal models (4,5,18,23). However, the precise mechanism has remained unclear yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is speculated that VitD3 derivatives may be useful for the therapy of Th1-dependent immune diseases. Indeed, recently, it has been reported that VitD3 derivative is effective against psoriasis in human and experimental autoimmune encephalomyelitis in animal models (4,5,18,23). However, the precise mechanism has remained unclear yet.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is an autoimmune disease, which is induced by abnormal acceleration of type-1 immune responses (14). Recently, it has been reported that topical 22-Oxa-1α,25-D 3 (maxacalcitol) is effective for the treatment of psoriasis (4,18). It remains unclear how VitD3 derivatives show their therapeutic effect against psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, vitamin D inhibits the activation of TNF alpha converting enzyme (TACE) [32]. TACE activation in renal cells gives rise to subsequent release of TNF-alpha, ICAM-1, and VCAM-1 into the circulation, promoting systemic inflammation.…”
Section: Cd4mentioning
confidence: 99%
“…However, activation of TACE can be blocked by active vitamin D preparations [33]. TACE activation is usually secondary to activation of the renal RAS system, which is also directly inhibited by VDR activation [32,34]. Thus, vitamin D suppresses TACE activation and subsequent inflammation on multiple levels.…”
Section: Cd4mentioning
confidence: 99%
“…A variety of studies have shown that oral vitamin D supplementation and vitamin D analogues have favorable clinical responses and maintain a similar safety profile to topical forms. Although patients did not experience adverse outcomes, the risk of hypercalcemia and bone demineralization is theoretically possible [38][39][40][41]. With the literature support for oral vitamin D, the next step is producing a vitamin D analog that can target the underlying pathophysiology of psoriatic lesions while minimizing adverse effects.…”
Section: Vitamin Dmentioning
confidence: 99%